Functionalized Gold Nanoparticles: Synthesis, Properties and Biomedical Applications. Issue 12 (24th September 2020) - Fan, Jianuo; Cheng, Yuqing; Sun, Mengtao
Abstract: Gold nanoparticles have excellent optical and plasmon properties and have enormous research potential when they combine with different ligands. Functionalized gold nanoparticles are widely used in drug delivery, biological detection, sensors, and even clinical treatment. At present, with the rapid development of functionalized gold nanoparticles, we think it is necessary to sort out the recent research results. In this paper, the synthesis, characteristics, and biological applications of the three aspects are introduced. Firstly, the synthetic methods of functionalized gold nanoparticles are reviewed, and the improvement of the commonly used synthetic methods is summarized. Then, the catalytic properties, oxidation resistance, and chirality optical properties are summarized in detail. Finally, we summarize the research progress in the field of biology in recent years. Abstract : This review provides a comprehensive overview of synthesis methods, properties, and biological applications of functional nanoparticles. The functionalized nanoparticles can play an significant role in the field of biology. Due to its good biocompatibility and adjustable stability, it has been successfully applied to biosensors, bioimaging, medical diagnosis and treatment.